2014
DOI: 10.1093/bioinformatics/btu031
|View full text |Cite
|
Sign up to set email alerts
|

InterProScan 5: genome-scale protein function classification

Abstract: Motivation: Robust large-scale sequence analysis is a major challenge in modern genomic science, where biologists are frequently trying to characterize many millions of sequences. Here, we describe a new Java-based architecture for the widely used protein function prediction software package InterProScan. Developments include improvements and additions to the outputs of the software and the complete reimplementation of the software framework, resulting in a flexible and stable system that is able to use both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5,443
2
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 6,811 publications
(5,764 citation statements)
references
References 28 publications
5
5,443
2
10
Order By: Relevance
“…First, we performed BLAST searches of taimen transcripts against several databases and found that 157,172 (82.5%) transcripts had significant sequence homology to the databases, and most (96.3%) were annotated with reference transcripts and proteins of Atlantic salmon (Lien et al., 2016) (Table 1). A homology search of the Pfam databases showed that 52,762 transcripts had at least one significant hit, and 79,800 transcripts were annotated using Interproscan (Jones et al., 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we performed BLAST searches of taimen transcripts against several databases and found that 157,172 (82.5%) transcripts had significant sequence homology to the databases, and most (96.3%) were annotated with reference transcripts and proteins of Atlantic salmon (Lien et al., 2016) (Table 1). A homology search of the Pfam databases showed that 52,762 transcripts had at least one significant hit, and 79,800 transcripts were annotated using Interproscan (Jones et al., 2014). …”
Section: Resultsmentioning
confidence: 99%
“…The sequences with significant hits in the Uniprot database or Pfam database were assigned GO terms using the Trinotate package, and the GO terms were assigned using Interproscan (Jones et al., 2014). Among the total transcripts, 72,728 transcripts were assigned to 15,107 GO terms, including 10,185 biological process terms, 1,429 cellular component terms, and 3,493 molecular function terms (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removed TE consisted of hits above the e‐value threshold of 1e‐5, with more than 40% of query coverage and longer than 100 nt. The gene models predicted by MAKER‐P were functionally analysed using InterProScan version 5.16.55 (Jones et al ., 2014) including annotation with Gene Ontology (GO) and biological pathway information. The InterProScan results were further parsed for additional functional evidence (GO terms and KEGG pathway) using interproscanParser script available at iPlant.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the FASTA2RDF, GeneCaller (a semantic wrapper for Prodigal (2.6.2) 17 ) and InterPro (interproscan-5.17-56.0) (a semantic wrapper for InterProScan 18 ) modules were used to handle and re-annotate the genome sequences. This resulted in 446 annotated genomes (7 × 60 genomes and 1 × 26 genomes) with provenance.…”
Section: Methodsmentioning
confidence: 99%